2019
DOI: 10.9734/jamb/2019/v15i430110
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Hepatitis E Virus in Dromedary Camels in the Sahelian Zone of West Africa

Abstract: Aim: This study was undertaken to determine the sero-epidemiological information and associated risk factors, of Hepatitis E virus (HEV) among dromedaries in Sub-sahelian region. Study Design: Cross sectional epidemiological survey. Place and Duration: The study was carried out in three countries of West Africa (Burkina Faso, Mali and Niger), over a two month period from February to March 2015. Methodology: A total of 133 serum samples collected from dromedaries (Camelus dromedarius) were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
6
3
Order By: Relevance
“…Similarly, a study conducted in Saudi Arabia found that all infected camels tested with RT-PCR were male (El-Kafrawy et al, 2022). Although our findings support the influence of gender on HEV infection in dromedary camels, some studies such as Li et al (2017) and Ouoba et al (2019) have not found any association between gender and HEV infection (Li et al, 2017;Ouoba et al, 2019).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Similarly, a study conducted in Saudi Arabia found that all infected camels tested with RT-PCR were male (El-Kafrawy et al, 2022). Although our findings support the influence of gender on HEV infection in dromedary camels, some studies such as Li et al (2017) and Ouoba et al (2019) have not found any association between gender and HEV infection (Li et al, 2017;Ouoba et al, 2019).…”
Section: Discussioncontrasting
confidence: 51%
“…( 2017 ) and Ouoba et al. ( 2019 ) have not found any association between gender and HEV infection (Li et al., 2017 ; Ouoba et al., 2019 ). Therefore, further studies on risk factors are required in this regard.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…El-Kafrawy et al ( 28 ) and Ouoba et al ( 17 ) could not find any effect of age on HEV seroprevalence in their sampled camels, in contrast to Bassal et al ( 31 ) who recoded a prevalence of 88.9% in camels aged 10 years and more, 56.0% in those of 7 years old and 67.4% in younger ones (3 years old). In addition, Li et al ( 29 ) and Sarani et al ( 36 ) reported young camels of 2 and 3 years old and those less than 2 years old as the most frequently positive (40.0, 36.4, and 100%, respectively).…”
Section: Discussionmentioning
confidence: 78%
“…All over the world, the seroprevalence of HEV infection in dromedary camels range from 8.3 to 62.9% ( 17 , 18 ). In Algeria, there are about 416.500 camels ( Camelus dromedarius ) raised following three breeding systems (sedentary, nomadic, and transhumant) in 9 Steppic and 8 Saharan provinces ( 19 ), where they occupy a crucial place in sustaining the livelihood of local and nomadic populations by participating to their food security, facilitating their displacements, and providing household incomes.…”
Section: Introductionmentioning
confidence: 99%